2022
DOI: 10.1093/jac/dkac025
|View full text |Cite
|
Sign up to set email alerts
|

Do antibiotics cause mitochondrial and immune cell dysfunction? A literature review

Abstract: While antibiotics are clearly important treatments for infection, antibiotic-induced modulation of the immune system can have detrimental effects on pathogen clearance and immune functionality, increasing the risk of secondary infection. These injurious consequences may be mediated, at least in part, through effects on the mitochondria, the functioning of which is already compromised by the underlying septic process. Here, we review the complex interactions between antibiotic administration, immune cell and mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 223 publications
0
10
0
1
Order By: Relevance
“…Moreover, it was recently shown that chitin metabolism pathways are regulated by the microbiome, which is consistent with the gene ontology analysis of the antibiotic constant condition ( Domin et al, 2023 ). One of the upregulated transcripts in the antibiotic constant treatment was Cytochrome C, which is central for mitochondrial function for ATP synthesis and apoptosis, suggesting that antibiotics can target metabolic processes within the host cells ( Miller & Singer, 2022 ). While antibiotic off target effects on Cytochrome C has not been described in N. vectensis, exposure of Oryzias latipes and Danio rerio to erythromycin, a macrolide, showed downregulation of Cytochrome C, as well as a variety of other metabolism-related genes, reduced locomotion, and energy metabolism ( Li & Zhang, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it was recently shown that chitin metabolism pathways are regulated by the microbiome, which is consistent with the gene ontology analysis of the antibiotic constant condition ( Domin et al, 2023 ). One of the upregulated transcripts in the antibiotic constant treatment was Cytochrome C, which is central for mitochondrial function for ATP synthesis and apoptosis, suggesting that antibiotics can target metabolic processes within the host cells ( Miller & Singer, 2022 ). While antibiotic off target effects on Cytochrome C has not been described in N. vectensis, exposure of Oryzias latipes and Danio rerio to erythromycin, a macrolide, showed downregulation of Cytochrome C, as well as a variety of other metabolism-related genes, reduced locomotion, and energy metabolism ( Li & Zhang, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Exposure of Branchiostoma belcheri , a cephalochordate, to antibiotics resulted in sublethal effects including immunosuppression and a reduction in eicosanoids ( Yuan et al, 2015 ). Moreover, antibiotics can directly affect the function and efficacy of mitochondria within the host cells ( Kovalakova et al, 2020 ; Miller & Singer, 2022 ; Singh, Sripada & Singh, 2014 ). While antibiotics can reduce and potentially kill bacteria in a host, the direct effects of these compounds on the host are understudied ( Baralla et al, 2021 ; Bojarski, Kot & Witeska, 2020 ; Yang, Song & Lim, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…So kommt es hier vermehrt zu einem Auftreten von bakteriellen Fehlbesiedelungen, was wiederum zu einer Begünstigung von Sekundärinfektionen führen kann [5]. Zudem wurde bereits ein möglicher Einfluss der Antibiotika auf die mitochondriale Funktion und damit auch auf das Immunsystem diskutiert [22]. Persistierende proinflammatorische Stimuli tragen konsekutiv zu einer progressiven immunsuppressiven Reaktion im Sinne eines aggravierten CARS bei, welches mit dem Zustand der Chronic Critical Illness (CCI) assoziiert wird.…”
Section: Lisowska Et Al Beschrieben In Einer Klinischen Studie Beispi...unclassified
“…Common examples include catecholamines, vasopressin or its analogues, corticosteroids and insulin. The stress response and immune function are also modified by other routine interventions, for example the use of immunomodulating sedative drugs [ 154 ] and a decrease in sympathetic activity due to the patient being asleep.…”
Section: Impact Of Hormonal Changes On Immune Cell Functionmentioning
confidence: 99%